Q-Rich Yeast Prion [PSI+] Accelerates Aggregation of Transthyretin, a Non-Q-Rich Human Protein - Verma, Meenakshi; Girdhar, Amandeep; Patel, Basant; Ganguly, Nirmal K.; Kukreti, Ritushree; Taneja, Vibha (Frontiers in Molecular Neuroscience, 2018)
Interactions amongst different amyloid proteins have been proposed as a probable mechanism of aggregation and thus an important risk factor for the onset as well as progression of various neurodegenerative disorders including Alzheimer’s, Parkinson’s, Huntington’s and Amyotrophic Lateral Sclerosis. Evidences suggest that transthyretin (TTR), a plasma protein associated with transthyretin amyloidosis or familial polyneuropathy (FAP) interacts with heterologous amyloid proteins including amyloid beta and islet amyloid polypeptide. In addition, recent clinical studies have revealed the presence of systemic polyneuropathy associated with FAP mutations in patients with spinocerebral ataxia, amyotrophic lateral sclerosis and new familial systematic prion disease. Hence, it is important to investigate the interactions amongst different amyloid proteins to gain better insight into the pathology of amyloid disorders. Yeast has been an excellent model system to study interaction/ cross-seeding between heterologous amyloid proteins, more because of presence of endogenous yeast prions. Here, we examined interactions of non-glutamine (non Q)-rich transthyretin, with glutamine (Q)-rich yeast prion protein Sup35. We established aggregation of an engineered double (F87M/ L110M) mutant M-TTR-GFP in yeast. This mutant is monomeric and readily formed aggregates compared to WT-TTR-GFP in yeast at acidic pH. Interestingly, aggregation of M-TTR-GFP was significantly enhanced in presence of [PSI+], an endogenous prion form of Sup35. Different variants of [PSI+] seeded M-TTR-GFP with different efficiencies and curing of [PSI+] (losing the prion form) in these strains reduced aggregation. Moreover, overexpression of prion domain of Sup35 fused to RFP (NM-RFP) also increased M-TTR-GFP aggregation. M-TTR-GFP and NM-RFP aggregates co-localized in perivacuolar and juxtranuclear region. Sup35 protein was even immunocaptured in M-TTR-GFP aggregates. However, M-TTR-GFP overexpression did not induce Sup35 aggregation. Thus, it appears to be a unidirectional interaction between these two amyloid proteins. However, no affect on M-TTR-GFP aggregation was observed due to another yeast prion, [PIN+]. Our findings thus show the molecular interaction of transthyretin with yeast prion and support that sequence similarity is not the prime requirement for heterologous amyloid interactions.